Neue Entwicklungen in der Kompressionstherapie - Reich-Schupke, Stefanie; Protz, Kerstin; Dissemond, Joachim; Rabe, Eberhard (DMW - Deutsche Medizinische Wochenschrift, 2017)
Patients with peripheral arterial occlusive disease who show an ankle arterial pressure of minimum 60 mmHg can be decongested by use of special padded bandages. Afterwards, medical compression stockings (class 1) with high strength and less elasticity are recommended. Mobile patients seem to benefit from progressive compression therapy with highest pressure above the calf. Compression after uncomplicated interventions of varicose veins or spider veins tends to be modified to a short and excentric compression in patients without risk factors. Valid datas are not available yet. Adaptive compression bandages show pros concerning efficiency, economy and more comfort for patients with edemas or ulcers.
Keywords: Kompressionstherapie; Druckgradient; Ödem; Ulcus cruris